Hydroxylated Chalcones as Aryl Hydrocarbon Receptor Agonists: Structure-Activity Effects. (2nd December 2020) - Park, Hyejin; Jin, Un-Ho; Karki, Keshav; Allred, Clinton; Davidson, Laurie A; Chapkin, Robert S; Orr, Asuka A; Nowshad, Farrhin; Jayaraman, Arul; Tamamis, Phanourios; Safe, Stephen
Abstract: Hydroxylated chalcones are phytochemicals which are biosynthetic precursors of flavonoids and their 1, 3-diaryl-prop-2-en-1-one structure is used as a scaffold for drug development. In this study, the structure-dependent activation of aryl hydrocarbon receptor (AhR)-responsive CYP1A1, CYP1B1, and UGT1A1 genes was investigated in Caco2 colon cancer cells and in non-transformed young adult mouse colonocytes (YAMC) cells. The effects of a series of di- and trihydroxychalcones as AhR agonists was structure dependent with maximal induction of CYP1A1, CYP1B1, and UGT1A1 in Caco2 cells observed for compounds containing 2, 2′-dihydroxy substituents and this included 2, 2′-dihydroxy-, 2, 2′, 4′-trihydroxy-, and 2, 2′, 5′-trihydroxychalcones. In contrast, 2′, 4, 5′-, 2′3′, 4′-, 2′, 4, 4′-trihydroxy, and 2′, 3-, 2′, 4-, 2′, 4′-, and 2′, 5-dihydroxychalcones exhibited low to non-detectable AhR activity in Caco2 cells. In addition, all of the hydroxychalcones exhibited minimal to non-detectable activity in YAMC cells, whereas 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin (TCDD) induced CYP1A1, CYP1B1, and UGT1A1 in Caco2 and YAMC cells. The activity of AhR-active chalcones was confirmed by determining their effects in AhR-deficient Caco2 cells. In addition, 2, 2′-dihydroxychalcone induced CYP1A1 protein and formation of an AhR-DNA complex in an in vitro assay. Simulation and modeling studies of hydroxylated chalcones confirmed their interactions with the AhR ligand-binding domain and were consistent with their structure-dependent activity as AhR ligands. Thus, this study identifies hydroxylated chalcones as AhR agonists with potential for these phytochemicals to impact AhR-mediated colonic pathways.